2006
DOI: 10.1111/j.1365-2184.2006.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of clove (Syzygium aromaticum) oil and its major components to human skin cells

Abstract: The essential oil extracted from clove (Syzygium aromaticum) is used as a topical application to relieve pain and promote healing in herbal medicine and also finds use in the fragrance and flavouring industries. Clove oil has two major components, eugenol and beta-caryophyllene, which constitute 78% and 13% of the oil, respectively. Clove oil and these components are generally recognized as 'safe', but the in-vitro study here demonstrates cytotoxic properties of both the oil and eugenol, towards human fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
131
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(151 citation statements)
references
References 24 publications
18
131
0
2
Order By: Relevance
“…In this study significant variations were observed at higher concentrations (150 and 200 mg/l) of the clove extracts. This result support the findings of Prashar et al [41], in roach, (Rutilus rutilus) exposed to clove powder. These alterations in blood variables may be due to cytotoxicity of clove extracts at higher concentrations.…”
Section: Resultssupporting
confidence: 93%
“…In this study significant variations were observed at higher concentrations (150 and 200 mg/l) of the clove extracts. This result support the findings of Prashar et al [41], in roach, (Rutilus rutilus) exposed to clove powder. These alterations in blood variables may be due to cytotoxicity of clove extracts at higher concentrations.…”
Section: Resultssupporting
confidence: 93%
“…These data are in agreement with the results from other studies (Prashar et al 2006). The major component of S. aromaticumis nomally considered to be eugenol, along with β-caryophyllene and lesser amounts of other components such as benzyl alcohol, however the proportions vary widely.…”
Section: Chemical Composition Of Crude Extractssupporting
confidence: 92%
“…Clove oil was found to be highly cytotoxic at concentrations as low as 0.03% (v/v) with up to 73% of this effect attributable to EU. beta-caryophyllene did not exhibit any cytotoxic activity, indicating that other cytotoxic components may also exist within the parent oil [54]. Volatile oils display cytotoxic action toward the human tumor cell lines PC-3 and Hep G2 50 [55].…”
Section: Anticancer Activity Of Phenylpropanoids Eu Scaffold and Itsmentioning
confidence: 93%
“…In this way, Atsumi and collaborators [56] compared the cytotoxicity of dehydrodiiso EU 28, alpha-di-iso EU 29, iso EU, EU, and bis-EU 30 in a gland tumor cell line (HSG) and normal human gingival fibroblasts (HGF). These compounds against the salivary gland tumor cell line (HSG) and normal HGF were greatest in dehydrodiiso EU 27 and alpha-di-isoeugenol 28, followed by isoeugenol, which showed greater activity than EU [54]. , respectively, suggesting that the presence of nitro and hydroxyl groups could be important in the activity of these compounds [55].…”
Section: Anticancer Activity Of Phenylpropanoids Eu Scaffold and Itsmentioning
confidence: 99%